The contribution of self-efficacy, self-esteem, social support, and self-concept to social anxiety of high school students in Malang city - Najich, Muhammad Ali; Rahman, Diniy Hidayatur; Atmoko, Adi; Setiyani, Oktafiana Dwi; Elsanadia, Oktolita (Universitas Negeri Yogyakarta, 2024)
Social anxiety has emerged as a prominent topic in mental health, particularly among high school students. This condition can arise due to concerns about making new friends and past experiences. This study aimed to examine the relationship between the following variables: (1) self-efficacy and social anxiety, (2) self-esteem and social anxiety, (3) social support and social anxiety, (4) self-concept and social anxiety, (5) the effect of self-efficacy on social anxiety through self-concept, (6) the effect of self-esteem on social anxiety through self-concept, and (7) the effect of social support on social anxiety through self-concept. This study employed a non-experimental, correlational design. The sample included 346 high school students in Malang City, selected through a cluster random sampling technique. Data collection utilized five instruments: the Social Anxiety Scale, General Self-Efficacy Scale (GSES), Rosenberg Self-Esteem Scale (RSES), Multidimensional Scale of Perceived Social Support (MSPSS), and Personal Self-Concept Scale (PSC). Path analysis was used to analyze the data. The results indicated that all paths had significance values below 0.05, suggesting that all hypothesized paths were significant. The findings of this study highlight the importance of counsellor guidance and counselling services in providing personalized coping strategies and emotional support to help students manage social anxiety effectively. For future researchers, these results may serve as a valuable resource, with a recommendation to explore additional variables affecting social anxiety and to expand the scope of the study area.